Oxygen-enriched fermentation improves the taste of black tea by reducing the bitter and astringent metabolites. (October 2021) - Chen, Lin; Liu, Fei; Yang, Yunfei; Tu, Zheng; Lin, Jiazheng; Ye, Yang; Xu, Ping
Graphical abstract: Highlights: Oxygen-enriched fermentation significantly improves the quality of black tea. Decreased catechins, flavonoid glycosides and phenolic acids can reduce astringency. Oxygen facilitated the oxidation of catechins, flavonoid glycosides and phenolic acids. Catechins oxidation accelerates the degradation of amino acids to form volatile aldehydes. Abstract: Oxygen involved fermentation is generally recognized as the critical process for the formation of quality of black tea. However, the specific role of oxygen plays in taste-related metabolites' alteration has not been illustrated clearly. In the present work, a series of fermentation systems with different oxygen concentrations were used to investigate the mechanism of the effects of oxygen on the quality and nonvolatile metabolites in black tea. The results showed that oxygen-enriched fermentation significantly improved the taste of black tea. And sixty-six metabolites, including catechins, theaflavins (TFs), proanthocyanidins, amino acids, flavonoid glycosides, and phenolic acids, were significantly different in the black teas fermented by three oxygen concentrations. Meanwhile, a 10–30% decrease in catechins, flavonoid glycosides and phenolic acids and a 5% increase in TFs, glutamate and glutamine in oxygen-enriched group, when compared to the control group, reduced astringency and bitterness and enhanced umami intensity. Furthermore, increased oxygen concentrations promoted the oxidation of catechins, flavonoid glycosides and some phenolic acids. And catechins oxidation in turn could accelerate the degradation of amino acids to form volatile aldehydes and also promote phenolic acids oxidation. Our results reveal the potential role of oxygen plays in the metabolites' alteration in black tea during fermentation, which gives a new insight into understanding the quality formation of black tea.